Effects of Soil Heterogeneity and Species on Plant Interactions - Li, Guoe; Wang, Mingxia; Ma, Chunyan; Tao, Rui; Hou, Fujiang; Liu, Yongjie (Frontiers in Ecology and Evolution, 2021)
Plant interactions are central in driving the composition, structure and diversity of plant populations and communities. Soil heterogeneity and species identity can modulate such interactions, yet require more studies. Thus, a manipulative experiment was conducted where three soil heterogeneity levels were developed by mixing local soil and sand in three different ratios (i.e. soil: sand ratio = 2:8, 5:5 and 8:2), and three typical species (i.e. Festuca elata, Bromus inermis, and Elymus breviaristatus) were used in different combinations. Soil heterogeneity was assumed to affect plant interactions, which were in turn modified by species. Plant height was applied as an indicator for plant interactions. Relative competition intensity (RCI) was used to quantify plant interactions, where RCI was applied as a ratio of monoculture and mixture performance. Results showed that soil heterogeneity and soil heterogeneity × species significantly affected RCI in mixtures compared with plant individuals growing alone (i.e. RCI1). However, species as a single factor did not affect RCI1. Moreover, species, and soil heterogeneity × species significantly affected RCI in mixtures compared with two individuals growing together (i.e. RCI2), and the difference between RCI1 and RCI2 (i.e. RCIdiff). Soil heterogeneity significantly affected RCI2 of F. elata. This study suggests that soil heterogeneity could buffer the stability of plant populations by modifying plant interactions, which would subsequently drive plant establishment. To explore the underlying mechanisms of such patterns, further studies considering more species and plant traits are needed.